Effects of annealing temperature and time on properties of composites based on Poly(lactic acid), microcrystalline cellulose and kenaf fiber - Alizadehmonir, Amir (2018)
The aim of this study was to produce PLA composites having a range of HDT above 130 °C. This was achieved by investigating the effect of heating rate, annealing conditions (temperature and time) and an addition of natural fillers namely microcrystalline cellulose (MCC) and kenaf fiber (KF) on the crystallinity and HDT of PLA. The ratio of PLA:filler was fixed to 70:30 (%w/w). The PLA/KF composites were melt-processed using a counter rotating twin screw extruder, whilst the PLA/MCC composites were produced using an internal mixer. Test specimens of PLA and PLA composites were compression moulded by a hot press machine. Differential scanning calorimetry (DSC) analysis of PLA sheet showed a marked crystallisation effect subjected to various heating rates as compared to that of as-received PLA resin. A heating rate of 10 °C/min had shown an intense crystallisation in the PLA sheet with a larger crystallisation peak and a double crystallisation melting peak. Crystallisation of PLA sheets was depended by both the annealing temperature and time, as observed in XRD patterns. A more intense and occurrence of multiple crystalline phases were achieved in the PLA sheets at a higher temperature and time. XRD was also used to calculate %crystallinity content, crystal phase and crystal size. POM-HS micrographs were utilized to provide evidence of crystallisation in the PLA and its composites. Annealed PLA composites were selected for HDT test and compared with their crystallinity. Annealed PLA/30%KF composite at 90 °C for 60 minutes was shown to have a higher HDT than PLA and PLA/30%MCC composites. By increasing annealing time, HDT decreased because extending time caused to create lots of petty crystals. The highest HDT of annealed PLA was obtained after heated at 110 °C for 60 minutes (71.2 °C). The maximum %crystallinity was attained in PLA/30%MCC annealed at 90 °C for 30 minutes (79.66%). The PLA/30%KF composite annealed at 110 °C for 60 minutes had the smallest crystallite size among all PLA composites and the maximum %crystallinity reached when PLA/30%KF annealed at 90 °C for 60 minutes (70.65%), demonstrating the highest HDT of 147.9 °C. This result shows that the presence of MCC and KF as a filler in PLA composites provides better HDT values than annealed neat PLA. The KF was shown to have a better nucleating ability than MCC based on the XRD and polarised optical microscopy studies. As a conclusion, sufficient annealing temperature and time, as well as effective filler, play the significant role in enhancing the crystallinity and HDT values in this study.